2007
DOI: 10.1038/sj.embor.7400902
|View full text |Cite
|
Sign up to set email alerts
|

ARC3 is a stromal Z‐ring accessory protein essential for plastid division

Abstract: In plants, chloroplast division is an integral part of development, and these vital organelles arise by binary fission from pre-existing cytosolic plastids. Chloroplasts arose by endosymbiosis and although they have retained elements of the bacterial cell division machinery to execute plastid division, they have evolved to require two functionally distinct forms of the FtsZ protein and have lost elements of the Min machinery required for Z-ring placement. Here, we analyse the plastid division component accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(159 citation statements)
references
References 26 publications
10
146
3
Order By: Relevance
“…Yeast two-hybrid and BiFC analyses suggested that AtCDP1 may participate in chloroplast division by interacting with ARC3, which is reported to be a stroma protein and localized to a ring at the midpoint of chloroplasts when the chloroplast division initiates [5,22,25]. In addition, ARC3 has an important role in chloroplast division because it interacts with AtFtsZ1 [25,32], AtMinD and AtMinE [25] at different locations of chloroplasts as shown by BiFC assay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yeast two-hybrid and BiFC analyses suggested that AtCDP1 may participate in chloroplast division by interacting with ARC3, which is reported to be a stroma protein and localized to a ring at the midpoint of chloroplasts when the chloroplast division initiates [5,22,25]. In addition, ARC3 has an important role in chloroplast division because it interacts with AtFtsZ1 [25,32], AtMinD and AtMinE [25] at different locations of chloroplasts as shown by BiFC assay.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli cell division site positioning system does not include such a protein. Furthermore, oscillation of MinD and MinE in higher plants has not been reported [12,13] and the genuine homolog of MinC has not been found in higher plants, despite that ARC3 is regarded as a MinC-like protein but its function is still not very clear [25]. Now, we show that AtCDP1, as a new component of the Min system, is involved in chloroplast division through the interaction with ARC3 at the early stage of chloroplast division process to ensure the constriction of the ring structure at the midpoint of chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would further imply that chloroplast Z ring dynamics should be regulated in part by factors that inhibit protofilament bundling. One candidate for such a factor is the chloroplast division protein ARC3, a proposed functional replacement for bacterial MinC (46,54), which was recently shown to inhibit lateral interactions between EcFtsZ protofilaments assembled in vitro (55).…”
Section: Discussionmentioning
confidence: 99%